Perencanaan Penjadwalan Perawatan Alat Berat Mobile Crane Menggunakan Metode CPM (Studi Kasus : PT. Menara Riau Perkasa) - Rozar Rayendra; Dedi Dermawan; Muhammad Qurthuby; Faradila Ananda Yul; Viona Aulia Rahmi; Indria Olyvhia Sinatra (SURYA TEKNIKA, 2024)
PT Menara Riau Perkasa is a company engaged in the rental of heavy equipment. The maintenance process unscheduled mobile crane heavy equipment is quite long within 5 days including overtime and rest hours and 1 day is inspection. Ordering heavy equipment for 6 days so that the company is often in a hurry for the maintenance process. Therefore, optimization of mobile crane maintenance is carried out by measuring the duration of each maintenance process using the Critical Path Method (CPM). This method is used to identify tasks needed in completing the project and determine scheduling flexibility. This method can complete the maintenance process with an effective time of 2.8 days with 8 hours of operation without rest hours and inspection for 1 day so that the total completion is 3.8 days. The use of the CPM method can reduce the maintenance process time because there are 2 main maintenance process activities that can be done at once with limited leeway time for the battery water process and hydraulic repairs.